The strategic role of human resource managers in shaping decision-making in Ethiopia - Tekalign Gidi Kure (PLoS ONE, 2025)
This study thoroughly examines the role of human resource managers in shaping decision-making within the manufacturing sector in Ethiopia. Employing a mixed-methods research design, data were gathered from 282 human resource directors using structured questionnaires and supplemented by 24 in-depth interviews. The quantitative analysis involved the use of descriptive statistics, the Kruskal-Wallis test, and the Mann-Whitney U test to explore orientations and differences across sectors, while qualitative data were analyzed using thematic analysis to capture the nuanced perspectives of Human Resource (HR) managers. The findings reveal a widespread recognition of HR as a strategic asset, with the majority of respondents advocating for greater integration of HR into organizational strategic planning. Nevertheless, the study uncovered significant sectoral disparities in the degree of HR managers’ involvement in strategic decision-making. Notably, the textile and clothing industries reported higher levels of HR representation in strategic discussions compared to the chemical and pharmaceutical sectors, where HR’s role was less pronounced. Additionally, the research identifies a critical gap in the formalization of HR strategies, with many organizations lacking documented, comprehensive HR plans. This absence of formalized HR frameworks limits the strategic potential of HR departments, restricting their ability to contribute effectively to organizational performance. The study underscores the critical need for bridging the gap between strategic intent and actionable HR practices is crucial for achieving sustained competitive advantage in the manufacturing sector.